The Hong Kong Statement on Practice Research 2017: Contexts and Challenges of the Far East. (January 2019) - Sim, Timothy; Austin, Michael; Abdullah, Fazlin; Chan, Tak Mau Simon; Chok, Martin; Ke, Cui; Epstein, Irwin; Fisher, Mike; Joubert, Lynette; Julkunen, Ilse; Ow, Rosaleen; Uggerhøj, Lars; et al.
This statement on social work practice research highlights the contributions of scholars, practitioners, and conference participants in the Fourth International Conference on Practice Research (ICPR) in 2017, hosted by The Hong Kong Polytechnic University in May 2017. It focuses on the contexts and challenges of carrying out practice research in the Far East and beyond as well as raises pertinent questions about the development of practice research. It begins with a brief description of the context of social work practice research in the Far East. The second part explores the organizational and community contexts and challenges of practice research with special attention to the perspectives of practitioners. It concludes with reviewing some of the continuing challenges that will guide the program planning for the Fifth ICPR in 2020 in Melbourne, Australia, located at the crossroads between East and West.